2011
DOI: 10.1103/physrevb.83.045409
|View full text |Cite
|
Sign up to set email alerts
|

Graphene adhesion on mica: Role of surface morphology

Abstract: We investigate theoretically the adhesion and electronic properties of graphene on a muscovite mica surface using the density functional theory (DFT) with van der Waals (vdW) interactions taken into account (the vdW-DF approach). We found that irregularities in the local structure of cleaved mica surface provide different mechanisms for the mica-graphene binding. By assuming electroneutrality for both surfaces, the binding is mainly of vdW nature, barely exceeding thermal energy per carbon atom at room tempera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(99 citation statements)
references
References 43 publications
5
91
2
1
Order By: Relevance
“…The calculated bandgap was about 3.2 eV, being much smaller than the experimental value of 7.85 eV. 23,24 Due to the well-known shortcomings of the DFT calculation in the generalized gradient approximation (GGA), our electronic structure underestimates the bandgap energy. Similarly, previous literature indicated that the DFT-calculated bandgaps are much smaller than experimentally measured ones for various semiconductors, including ZnO and ZrO 2 (Supporting Information, Text S1).…”
Section: ■ Results and Discussionmentioning
confidence: 68%
“…The calculated bandgap was about 3.2 eV, being much smaller than the experimental value of 7.85 eV. 23,24 Due to the well-known shortcomings of the DFT calculation in the generalized gradient approximation (GGA), our electronic structure underestimates the bandgap energy. Similarly, previous literature indicated that the DFT-calculated bandgaps are much smaller than experimentally measured ones for various semiconductors, including ZnO and ZrO 2 (Supporting Information, Text S1).…”
Section: ■ Results and Discussionmentioning
confidence: 68%
“…When in contact with the mica surface graphene conserves its unique properties27, even when mica has been shown to induce doping of graphene1526. In a previous study we have shown that graphene above the double water layer is only slightly n-type doped.…”
Section: Resultsmentioning
confidence: 94%
“…Here, the authors argued in favour of a Kondo effect with full screening, as three conductionband channels coupled to the impurity spin. Finally, in a refined quantum-chemical calculation [19] based on a complete active-space self-consistent field approach, albeit on small clusters, it was found that Co in an h position favours a higher-spin state of S = 3/2.…”
Section: Magnetic Adatoms On Graphenementioning
confidence: 98%